Ecotourism, Conservation Mangement, and Regional Government Autonomy - Sambas Basuni (Media Konservasi, 2001)
At the end decade of 20 th century, the rate of world tourism development was related to "nature-oriented"  travelling so high. In tourism terminology, this travelling is conceived as ecotourism. Almost all countries  in the world respond to this new concept of tourism enthusiastically, in particular, developing countries which rich with natural areas with regard to foreign exchange from international tourists. Unfortunatelly, those natural areas are protected areas which designated as such because of intrinsically unique, beautiful, high biodiversity, and ecologically fragile. The use  of these protected areas are limited to conserve is natural conditions. This paper emphasize the need of us to guard against this new concept of tourism, review of ecotourism concept from ecological perspective; the relationship between conservation management authority and regional otonomy.